Association of vitamin D receptor gene FokI and TaqI polymorphisms and risk of RDS. (1st November 2020) - Ustun, Nuran; Eyerci, Nilnur; Karadag, Nilgun; Yesilyurt, Ahmet; Zenciroglu, Aysegul; Okumus, Nurullah
Abstract: Background: Vitamin D and its receptor (VDR) have important roles in perinatal lung development. The objective of this study was to investigate the possible association between VDR FokI and TaqI polymorphism and development of respiratory distress syndrome (RDS) in preterm infants. Method: A total of 173 premature infants <34 weeks: 82 with RDS and 91 without RDS were enrolled. Genotyping of VDR polymorphisms was assayed by real-time PCR. Serum 25-hydroxyvitamin D (25-OHD) levels were measured by ELISA in blood samples that were obtained at the time of admission to the neonatal intensive care unit. Results: Gestational age (GA) was significantly lower in the RDS group compared with the controls. In univariate analysis, VDR TaqI CT and CC genotypes were associated with the increased risk of RDS (OR = 3.264, p = .001, 95% CI = 1.597–6.672 and OR = 5.222, p < .001, 95% CI = 2.165–12.597, respectively); while VDR FokI showed no association with RDS. In multivariate logistic regression analysis, variant TaqI genotype increased risk of RDS ( p = 0.001, OR = 3.464, 95% CI = 1.655–7.251) independent of gestational age, birth weight and gender. 25-OHD levels in the RDS group were significantly lower compared with those in without the RDS group ( p = .002). Serum 25-OHD levels were not significantly different among the different FokI and TaqI genotypes in RDS group. Conclusions: This is the first report of association of VDR polymorphism with RDS development in preterm neonates. Current study suggests that VDR TaqI polymorphism may be involved in predisposition to RDS in premature neonates. Further studies are needed to assess the contribution of vitamin D and VDR signaling to the pathogenesis RDS